Management of Learning of English Subjects Based on Ministry of Education Number 371/M/2021 At Madrasah Ibtidaiyah - Susilo Surahman (Linguanusa : Social Humanities, Education and Linguistic, 2023)
Introduction to The Problem : The syllabus is the primary reference in preparing the Learning Implementation Plan (RPP). The readiness of the syllabus will also impact the preparedness of the RPP because the syllabus first shows the purpose of learning to be implemented. Purpose : This research aims to explain the management of English learning in Madrasah Ibtidaiyah Walikukun Academic Year 2022/2023 through syllabus preparation. The research was conducted at Madrasah Ibtidaiyah Muhammadiyah Pojok Walikukun Widodaren Ngawi East Java. Design/methods/approach: This research is a qualitative research with a field approach (Field Research). Sources of primary data obtained through observation, interviews, and documentation. Respondents amounted to 10 people from 5 schools in Central Java. Data analysis by triangulation through data reduction, presentation; and conclusion. Findings: Research results show that the management functions applied in English learning subjects are learning planning, organization of learning, and mentoring-evaluation-development. Second, the syllabus compiled at Madrasah Ibtidaiyah Walikukun in the Academic Year 2022/2023 is divided into 2 (two), namely: Thematic Syllabus of English Class and Thematic Syllabus of English Outside the Classroom. Research : implications/limitations: This research provides suggestions for future researchers to deepen research, especially related to the evaluation of the implementation of management in English subjects at school. Originality/value: This study found an important finding that the management of English subjects for students has two important things, namely the existence of a good learning system and a good syllabus that contains material in class and outside the classroom.